已知f(x)=(x^2013+ax^2011+bx^2009)-8,且f(-2)=10,则f(2)=?
1个回答
-26
f(-2)+8=(-2^2013+a-2^2011+b-2^2009)=-(2^2013+a2^2011+b2^2009)=-[f(2)+8]=18
得出f(2)=-26
相关问题
已知函数f(x)=ax^2011+bx^2013,则f(1/2)+f(-1/2)=
已知函数f(x)=x^5+ax^3+bx-8且f(-2)=10.则f(2)=
f(x)=ax^2013+bx^2011+,且f(2)=3 问:f(-2)?
已知f(x)=x^2+asinx+bx+8,且f(-2)=10,则f(2)=______________
已知函数f(x)=ax^7+bx+(c/x)-2,若f(2009)=10,则f(-2009)的值
已知f(x)=x^5+ax^3+bx+8,且f(-2)=10,求f(x)
已知函数f(x)=ax^3+bx+2,且f(2)=8,则f(-2)=?
已知函数f(x)=ax3+bx+8,且f(-2)=10,则f(2)的值是( )
已知f(x)=x5+ax3+bx-8,且f(-2)=10,那么f(2)等于( )
已知f(x)=x5+ax3+bx-8,且f(-2)=10,那么f(2)等于( )